Bringing the individual back in: a normative argument for human security. - Layug, Allan S. (2008)
Despite the prevalence of human security discourses, there has been an insufficient argumentation on why the individual should be the referent of security. This insufficiency leads to a central question of human security not being addressed, “Why human security?” On the one hand, this oversight or inattention has been grounded on the proclivity of proponents of individual-centered human security to just assume that the individual matters without arguing for it. On the other, there is the utter disregard of the primacy of the individual from those who cling to society-centered human security approach. This paper claims that both assumption and utter disregard of why we need to reference security on the individual is not unproblematic. Bringing the individual back in, as it were, has to do with a normative argument, not wishy-washy claims. The central argument is that the value of the individual founded on human freedom, well-being, and dignity grounds the reasons why, indeed, we should care about human security.